ISLAM NUSANTARA: MODERASI ISLAM DI INDONESIA - Mubarok, Ahmad Agis; Rustam, Diaz Gandara (Journal of Islamic Studies and Humanities, 2018)
This paper aims to find out the character of Islam Nusantara, as a manifestation of the existence of moderate Islam that was taught by the Walisongo and religious figures to this day. The historical phenomenology is employed to understand Islam Nusantara. The results of this research showed that Islam in Nusantara has five special characters. First, Islam Nusantara is always in accordance with their contexts. Second, it has a tolerant attitude towards differences. Third, it appreciates traditions that have long existed before. Fourth, it has a progresive attitude towards the progress of time. Fifth, it emancipates. AbstrakTulisan ini bertujuan untuk mengetahui karakter Islam Nusantara,sebagai wujud adanya adanya Islam moderat yang diajarkan oleh para Walisongo dan tokoh-tokoh agama hingga saat ini. Penulis menggunakan pendekatan historis fenomenologis. Hasil penelitian ini menunjukkan bahwa Islam di Nusantara memiliki lima karekter. Pertama, Islam Nusantara selalu sesuai dengan konteks zaman. Kedua, ia mengambil sikap toleran terhadap perbedaan. Ketiga, ia menghargai tradisi yang telah lama ada sebelumnya. Keempat, ia bersikap progresif terhadap kemajuan zaman. Kelima, ia membebaskan.